THE MODEL OF MOTHERS’ BEHAVIOR WHO PARTICIPATE IN “BINA KELUARGA BALITA” PROGRAM IN SULAWESI, INDONESIA - Shine Pintor Siolemba Patiro; Sakina Nusarifa Tantri; Steviani Batti; Wijanarko Wijanarko (Sosiohumaniora, 2022)
ABSTRACT. The high mortality rate of toddler in Parigi Moutong Regency of Central Sulawesi and Sinjai Regency of South Sulawesi province is one of the problems that caused the attention to conduct this study. This study aims to reveal the role of attitudes, subjective norms, and perceived behavioral control in predicting and explaining the intentions and behavior of mothers in those areas who have toddlers to participate in the Toddlers Development Program through the implementation of the Theory of Planned Behavior (TPB). This study used an exploratory sequential design involving 300 respondents obtained through purposive sampling. The data is collected using a questionnaire which was analyzed using SEM analysis with the help of IBM SPSS AMOS 23. The results showed that TPB model which was developed in explaining and predicting the mothers behavior who have toddlers in those areas in participating of the BKB program is as expected. The behavior of participating program is significantly influenced by the intention to participate in the BKB program. The intention to participate in the BKB program was significantly influenced by: attitudes towards participation in the BKB program, subjective norms regarding participation in the BKB program, and perceived behavioral control towards participation in the BKB program. The variable that contributes the most to influence the intention to participate in the program is the attitude towards participation in the BKB program. Limitations of this study is uncovered as well.